2000
DOI: 10.1046/j.1365-2265.2000.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP21 analysis and phenotype/genotype relationship in the screened population of the Italian Emilia–Romagna region

Abstract: The high frequency of genotypes 'null' or 'A' in the 'phase A' vs. 'phase B' of our study confirms the usefulness of neonatal screening in preventing the death of male patients with salt wasting forms. The substantial similarity in the mutational spectrum of classical forms found in our study, based on the detection of all the classical patients of a specific area, leads us to believe that the distribution of mutations is due to the inherent characteristics of the gene locus, and that regional effects play a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 32 publications
(40 reference statements)
8
25
1
Order By: Relevance
“…The mutations in patients from the Emilia-Romagna province in northern Italy reported herein had a large deletion on only 3% of their 106 alleles. A previous report from Emilia-Romagna by Balsamo et al found 13% of 114 alleles with the large deletion mutation [39]. This is surprising as these patients originated from the same region in Italy.…”
Section: Discussionmentioning
confidence: 55%
“…The mutations in patients from the Emilia-Romagna province in northern Italy reported herein had a large deletion on only 3% of their 106 alleles. A previous report from Emilia-Romagna by Balsamo et al found 13% of 114 alleles with the large deletion mutation [39]. This is surprising as these patients originated from the same region in Italy.…”
Section: Discussionmentioning
confidence: 55%
“…The overall frequency of p.V281L is however one of the highest found for this mutation both in Greek [18] and other populations in Europe and the Mediterranean area [19,20,21,22,25,35,36,48,49,50,51]. This mutation is quite common in our population.…”
Section: Discussionmentioning
confidence: 90%
“…This mutation is also the most common worldwide, except in some groups of patients of South Europe (Portugal, Italy and Spain), where it is less common and where mutation V281L has been identified as the most prevalent. Mutation V281L, which confers more than 20% enzymatic activity, is the most common variant associated to the nonclassical form of 21-OH deficiency in South European countries, reaching 34% in Spain (Ezquieta et al, 2002), 28% in Portugal (Friaes et al, 2006) and 24% in Italy (Balsamo et al, 2000). In North Europe, the most frequent mutation in NC alleles is P30L (Table 2).…”
Section: Discussionmentioning
confidence: 99%